THE INVESTIGATION OF TERMINOLOGY AND ITS SPECIFIC FEATURES (Conferencea, 2022)
This article deals with the problems of terms and terminology which studies linguistic, stylistic and other characteristic features of terms in Modern English. It also investigates different viewpoints of terms by scholars in the world linguistics.